Fast and Efficient Bromination of Aromatic Compounds with Ammonium Bromide and Oxone - Naresh, Mameda; Arun Kumar, Macharla; Mahender Reddy, Marri; Swamy, Peraka; Nanubolu, Jagadeesh Babu; Narender, Nama (Synthesis, 2013)
A highly efficient, rapid and regioselective protocol was developed for the ring bromination of aromatic compounds under mild conditions with ammonium bromide as a source of bromine source and Oxone® (potassium peroxysulfate) as an oxidant. No metal catalyst or acidic additive is required. A variety of aromatic compounds, including methoxy, hydroxy, amino, and alkyl arenes, reacted smoothly to give the corresponding monobrominated products in good to excellent yields in very short reaction times. Moreover, dibromination of deactivated anilines to give the corresponding dibromides proceeded in high yields. Interestingly, 1-(2-naphthyl)ethanone provided a ring-brominated product.
Keywords: halogenation; bromination; arenes; regioselectivity; aryl halides